Using bentonite for NPP liquid waste treatment - Bui , Dang Hanh (Nuclear Science and Technology, 2015)
During operation, nuclear power plants (NPPs) release a large quantity of water waste containing radionuclides required treatment for protection of the radiation workers and the environment. This paper introduces processes used to treat water waste from Paks NPP in Hungary and it also presents the results of a study on the use of Vietnamese bentonite to remove radioactive Caesium from a simulated water waste containing Cs